PRODUCTIVITY POTENTIAL OF ELEPHANT FOOT YAM (AMORPHOPHALLUS PAEONIIFOLIUS (DENNST.) NICOLSON) IN ALFISOLS AS INFLUENCED BY FERTILITY LEVELS - BISWANATH SAHOO,; M. NEDUNCHEZHIYAN,; PINAKI ACHARYYA, (The Bioscan, 2015)
The field experiment was carried out for consecutive two years during 2011-12 and 2012-13 to study the effect of fertility management practices on elephant foot yam which revealed that application of FYM 25 t/ha alone or N-P2O5-K2O 100-60-100 kg/ha + FYM 10 t/ha resulted in tall and wider spread plants. Application of N-P2O5-K2O 100-60-100 kg/ha + FYM 10 t/ha resulted in higher corm diameter (25.55 cm), corm yield/plant (2159 g/plant) and corm yield/ha (37.6 t/ha). The yield attributes and yield with the application of N-P2O5-K2O 100-60-100 kg/ ha + FYM 10 t/ha were on par with the application of FYM 25 t/ha. Higher corm bulking rate at early stage (8.32- 9.11 g/day) followed by higher corm bulking efficiency (437.50%) led to higher corm yield with the application of N-P2O5-K2O 100-60-100 kg/ha + FYM 10 t/ha. Hence, the fertilizer level N-P2O5-K2O 100-60-100 kg/ha + FYM 10 t/ha may be recommended for farmers growing elephant foot yam under irrigated alfisols.